MAIT cells: new guardians of the liver - Kurioka, A; Walker, L; Klenerman, P; Willberg, C (Nature Publishing Group, 2016)
The liver is an important immunological organ that remains sterile and tolerogenic in homeostasis, despite continual exposure to non-self food and microbial-derived products from the gut. However, where intestinal mucosal defenses are breached or in the presence of a systemic infection, the liver acts as a second 'firewall', because of its enrichment with innate effector cells able to rapidly respond to infections or tissue dysregulation. One of the largest populations of T cells within the human liver are mucosal-associated invariant T (MAIT) cells, a novel innate-like T-cell population that can recognize a highly conserved antigen derived from the microbial riboflavin synthesis pathway. MAIT cells are emerging as significant players in the human immune system, associated with an increasing number of clinical diseases of bacterial, viral, autoimmune and cancerous origin. As reviewed here, we are only beginning to investigate the potential role of this dominant T-cell subset in the liver, but the reactivity of MAIT cells to both inflammatory cytokines and riboflavin derivatives suggests that MAIT cells may have an important role in first line of defense as part of the liver firewall. As such, MAIT cells are promising targets for modulating the host defense and inflammation in both acute and chronic liver diseases.